2005
DOI: 10.1037/0882-7974.20.4.695
|View full text |Cite
|
Sign up to set email alerts
|

Training effects on dual-task performance: Are there age-related differences in plasticity of attentional control?

Abstract: A number of studies have suggested that attentional control skills required to perform 2 tasks concurrently become impaired with age (A. A. Hartley, 1992; J. M. McDowd & R. J. Shaw, 2000). A. A. Hartley (2001) recently observed that the age-related differences in dual-task performance were larger when the 2 tasks required similar motor responses. The present study examined the extent to which age-related deficits in dual-task performance or time sharing--in particular, dual-task performance of 2 discrimination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

36
268
4
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 261 publications
(312 citation statements)
references
References 33 publications
36
268
4
4
Order By: Relevance
“…Similarly, training of executive control produced some promising results in the past (e.g., Bherer et al, 2005;Karbach & Kray, 2009;Kramer, Larish, & Strayer, 1995;see Noack et al, 2009 for reviews) motivating further investigation of the trainability of this ability (n = 16). Thirteen of the 16 studies reported data from older samples while, for example, only 9 of the 35 studies on working memory reported data from older samples.…”
Section: Study Sample Overview Training Targetsmentioning
confidence: 99%
“…Similarly, training of executive control produced some promising results in the past (e.g., Bherer et al, 2005;Karbach & Kray, 2009;Kramer, Larish, & Strayer, 1995;see Noack et al, 2009 for reviews) motivating further investigation of the trainability of this ability (n = 16). Thirteen of the 16 studies reported data from older samples while, for example, only 9 of the 35 studies on working memory reported data from older samples.…”
Section: Study Sample Overview Training Targetsmentioning
confidence: 99%
“…By contrast, another sequential training protocol administered on different days led to comparable gains when compared to single-modality cognitive training on measures of EFs and episodic memory (Shatil 2013). Desjardins-Crépeau et al (2016) also failed to find synergistic effects of sequential multimodal training utilizing Bherer et al's (2005) DT training protocol and moderate-intensity aerobic training administered on separate days.…”
Section: Multimodal Approaches: Combining Cognitive and Aerobic Trainingmentioning
confidence: 95%
“…For example, working memory training has led to significant transfer gains in EFs in both young and older adults (Baniqued et al 2015;Brehmer et al 2012;Morrison and Chein 2011;Rhodes and Katz 2017). Similarly, dual-task (DT) training has led to cross-modality near-transfer, (Bherer et al 2005(Bherer et al , 2006(Bherer et al , 2008Desjardins-Crépeau et al 2016;Erickson et al 2007aErickson et al , 2007bLussier et al 2015Lussier et al , 2016, upregulation and increased efficiency in prefrontal regions in younger and older adults (Erickson et al 2007a, b), and improved balance and mobility (Li et al 2010). Such DT training is thought to improve processes such as task coordination and working memory (Bherer et al 2005).…”
Section: Single-modality Trainingmentioning
confidence: 99%
See 1 more Smart Citation
“…A behavioral study showed that training can also improve dual-tasking in older adults. Bherer et al (2005) showed that training improved dual-task performance in both older and younger adults. The improvement also generalized to novel task combinations.…”
mentioning
confidence: 99%